2016
DOI: 10.17219/acem/42414
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a 3-Week Low-Calorie Diet and Balneological Treatment on Selected Coagulation Parameters in Morbidly Obese Patients

Abstract: is greater than energy expenditure, causing both the hyperplasia and the hypertrophy of adipocytes. Adipocyte hypertrophy has negative consequences connected with insulin resistance and chronAccording to the World Health Organization (WHO), obesity is related to an excessive accumulation of adipose tissue, which may result in health deterioration [1]. This occurs when energy input AbstractBackground. The most common cause of death among people with obesity are cardiovascular complications as a result of a hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…38,40,41 In line with this, several studies have compared a number of hemostatic biomarkers in people with obesity and normal weight. These studies conclude that obesity is accompanied by increased levels of biomarkers of endothelial function, e.g., t-PA:Ag and von Willebrand factor (vWF), [42][43][44][45][46] coagulation, e.g., fibrinogen, FVII, TF, factor IX (FIX), factor X (FX), factor XII (FXII), F1 þ 2, thrombin-AT complexes (TAT), Ddimer, 34,42,44,45,[47][48][49][50][51][52] and impaired fibrinolysis, for example, PAI-1 42,43,45,46,51,53 and TAFI. 54,55 Interestingly, it has been suggested that obesity is accompanied by elevated concentrations of coagulation inhibitors, such as protein C, AT, and TFPI, 38,52,56 perhaps as a protective response toward the increased thrombotic risk in obesity.…”
Section: Obesity and The Hemostatic Balancementioning
confidence: 99%
“…38,40,41 In line with this, several studies have compared a number of hemostatic biomarkers in people with obesity and normal weight. These studies conclude that obesity is accompanied by increased levels of biomarkers of endothelial function, e.g., t-PA:Ag and von Willebrand factor (vWF), [42][43][44][45][46] coagulation, e.g., fibrinogen, FVII, TF, factor IX (FIX), factor X (FX), factor XII (FXII), F1 þ 2, thrombin-AT complexes (TAT), Ddimer, 34,42,44,45,[47][48][49][50][51][52] and impaired fibrinolysis, for example, PAI-1 42,43,45,46,51,53 and TAFI. 54,55 Interestingly, it has been suggested that obesity is accompanied by elevated concentrations of coagulation inhibitors, such as protein C, AT, and TFPI, 38,52,56 perhaps as a protective response toward the increased thrombotic risk in obesity.…”
Section: Obesity and The Hemostatic Balancementioning
confidence: 99%
“…Others, such as cancer, ischemic heart disease with myocardial infarction, or cerebral stroke, pose a serious threat to life. The last two complications are major causes of death of subjects with morbid obesity (Firszt-Adamczyk et al 2016; World Health Organization Obesity Technical report series No: 894 Obesity: Preventing and managing the global epidemic. 2000).…”
Section: Introductionmentioning
confidence: 99%
“…There are many methods used such as diet treatments, exercise treatments, drug treatments, and surgical interventions (Ricci et al 2016). These treatments include balneotherapy (Fioravanti et al 2015a;Firszt-Adamczyk et al 2016;Hanh et al 2012;Jokic et al 2018;Matsumoto 2018;Olah et al 2011;Rapolienė 2016;Rosc et al 2015), which traditionally involves immersion in mineral and/or thermal waters from natural springs, but may interchangeably be defined as balneological interventions with natural gases (CO 2 , sulfur and radon, etc. ), peloids (mud) and other traditional remedies (for example, hay), whereas hydrotherapy generally employs normal tap water for medical treatment (Fioravanti et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in obese individuals, fibrinolysis is inhibited. A direct relationship has been established between morbid obesity and an increased level of tissue factor, blood coagulation factors VII and VIII, von Willebrand factor, antithrombin III, TAT complex and fibrinogen and, indirectly, endothelial damage as an independent factor contributing to the risk of thrombosis [24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%